KAMPANYE KEBERSIHAN LINGKUNGAN MELALUI PROGRAM KERJA BAKTI MAHASISWA PROGRAM STUDI MANAJEMEN DI KELURAHAN POTULANDO, KECAMATAN ENDE TENGAH, KABUPATEN ENDE - Maria Helena Carolinda Dua Mea (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
Environmental cleanliness is a vital issue in social life, especially the people of Ende Regency. To help overcome the problem of waste in community settlements, an environmental cleanliness campaign was carried out through community service activities by the academics of the Management Study Program of the University of Flores. The purpose of this community service activity with community service is to campaign for the importance of environmental cleanliness to the people of Potulando Village, Ende Tengah District, Ende Regency, help overcome environmental cleanliness problems in the Potulando Village community, train students to have a caring attitude towards nature and the environment, and make Tri Higher Education Dharma. This activity is a Community Service Activity carried out by students of the 2016 and 2017 Flores University Management Study Program. The activity was carried out in the Potulando Village area, Ende Tengah Subdistrict, Ende Regency on November 12, 2019. This environmental cleanliness campaign activity was carried out using the voluntary cleaning work method. environment and collection and sorting of waste types. Environmental cleanliness campaign activities begin with environmental cleaning activities, namely by cleaning roads from wild plants that grow on the roads and sidewalks, then cleaning the gutters from accumulated garbage. Waste sorting is carried out by sorting waste based on its type, namely organic waste and inorganic waste.